Implementasi Strategi Promosi Penjualan dalam Perspektif Integrated Marketing Communication (IMC) pada Produk Sampoerna di Masa Pandemi Covid-19 (Studi Kasus pada Sampoerna Retail Community (SRC) Hikmah Mart Rayon Ngancar Kediri) - Mega Alfiyah Khasanah; Dhiyan Septa Wihara; Amat Pintu Batu (POLITEKNIK CAHAYA SURYA, 2020)
One indicator of a successful company is how its strategy to increase sales. PT HM Sampoerna, one of the cigarette producers in Indonesia, has carried out a unique strategy during the co-19 pandemic. The purpose of this study is to determine the application and factors that support the success of sales promotion strategies in the perspective of Integrated Marketing Communication on Sampoerna products during the covid-19 pandemic. This type of descriptive qualitative research was taken to obtain information from 3 informants namely owner of SRC Hikmah Mart, Ngancar sales coordinator and consumers. In addition, a qualitative approach is expected to reveal the extent of the implementation of the strategy. The validity and reliability of this study uses source triangulation. Data analysis techniques in this study consisted of 3 stages, namely: data reduction, data presentation, and drawing conclusions. The results showed that one of SRC Hikmah Mart's strategies was to enable delivery order services, provide facilities for covid prevention, and routine monitoring through social media by sales. So that Sampoerna cigarette products do not experience a significant decrease. High stress levels, lots of free time and the assumption that cigarettes consumed are determinants of social class and income. So the tendency for smoking is greater, because consumers continue to smoke even though the type of cigarettes purchased is cigarettes whose price is cheaper than before the co-19 pandemic.Keywords: Promotion Strategy, Sampoerna Products, Pandemic Covid-19, Sampoerna Retail Communities (SRC)